Anthoceros subtilis and A. telaganus (Anthocerotaceae): two new records for America from the hornwort flora of Mexico - Ibarra-Morales, Ariadna (Phytotaxa, 2021)
In a recent trip to southern Mexico, Anthoceros subtilis and A. telaganus were recorded for the first time in Mexico and the American continent. Several previous records of A. subtilis were from Asia and one from Africa, and A. telaganus is known only from Indonesia. The new range extension of these two species is reported and the species are described and illustrated.                Mexican populations of A. subtilis are characterized by small brown spores (26–42 μm), similar ornamentation on proximal and distal spore surfaces with papillate to tuberculate projections. Anthoceros telaganus is characterized by larger black spores (32–53 μm) with a smooth strip along the trilete mark on the proximal surface. Molecular genetic sequencing is needed to test whether Asian and American populations of these morphologically similar but geographically disjunct taxa are conspecific.